Nasogastric tube insertion in anesthetized intubated adult patients: A comparison between the “reverse Sellick’s maneuver with throat pack in situ” and reverse Sellick’s maneuver alone - Roy, Mrinal Kanti; Maitra, Sanjay; Mandal, Sangita; Arpita Laha,; Mandal, Mohanchandra (Asian Journal of Medical Sciences, 2023)
Background: Nasogastric tube (NGT) insertion is an essential procedure in the operating room for which the anesthesiologists often take the responsibility. This simple procedure often becomes difficult in anesthetized patients. Literature reveals the flooding of studies and novel techniques are in the pipeline, indicating that quest for the best is still on. Aims and Objectives: The aim of the study was to determine the proportion of patients in whom successful NGT insertion would be possible in the first attempt using either the “Reverse Sellick’s maneuver (RSM) with throat pack in situ” technique or RSM alone; and to compare the proportions between the two groups. Materials and Methods: This interventional study was performed on 222 adult patients (≥18 years), undergoing abdominal surgeries requiring intraoperative NGT insertion. Patients received NGT insertion using the combined RSM with “throat pack in situ” technique (Group A, n=111) or RSM alone (Group B, n=111). The proportion of patients in whom successful NGT insertion was possible in the first attempt using either of the techniques and the time taken for correct placement of NGT in both the groups. In addition, the incidence of adverse events was noted. Results: Although, NGT placement was possible in higher proportions of patients in Group A in first attempt compared with Group B (91% vs. 83.8%), it was not significant on analysis (P=0.106). The procedure time in both the groups was comparable (30.0±4.0 vs. 29.9±4.3, P=0.859). Coiling was found to be significantly more in the RSM alone technique as compared to the combined method. (P=0.04). Conclusion: With comparable success rate and lesser incidence of adverse events, it can be commented that the RSM with throat pack in situ technique appears to be a better alternative to RSM alone.